INNOVATIVE TECHNOLOGIES AS A TOOL FOR OPTIMISING THE MARKETING STRATEGY OF ORGANIC MARKET OPERATORS - SAVYTSKA, Nataliia; PAKHUCHA, Ellina; BONDARENKO, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on optimizing the marketing strategy of organic market operators through the implementation of innovative technologies as a crucial tool to enhance their competitiveness in the context of economic digitalization and changing market challenges. Since organic market operators face numerous challenges, including high competition, dynamic consumer preferences, and the need to adapt to business digitalization, innovative technologies have become a key instrument for effective product promotion, strengthening market positions, and achieving sustainable development.The advantages and disadvantages of using innovative technologies in the marketing activities of organic market operators were analyzed. This analysis led to the conclusion that innovative technologies in marketing offer significant opportunities for organic market operators. However, their implementation requires thorough planning, preparation, and risk assessment to minimize drawbacks and maximize potential benefits. The article examines the most effective marketing strategies utilized in the organic product market, emphasizing the unique features of the organic market. Special attention is paid to the organic nature and quality of products, transparency of production processes, and responsibility toward consumers. It has been determined that marketing strategies in the organic product market are not only a means of product promotion but also a tool for creating value for consumers, building long-term relationships, and achieving sustainable development. Based on the conducted research, innovative technologies for optimizing marketing strategies in the organic product market have been developed. Particular attention is given to areas and technologies such as digital marketing and automation, e-commerce and mobile applications, blockchain, innovative advertising approaches, sustainable marketing, and the Internet of Things (IoT). As a result, innovative technologies not only optimize marketing strategies but also create additional value for consumers, providing a competitive advantage for organic market operators. These technologies serve as a tool to ensure sustainable development that meets the challenges of the modern market.
Keywords: innovative technologies; optimisation; organic market; digital marketing; competitiveness; marketing strategy; promotion tools; marketing efficiency